The legal powers of the military police in the enforcement of military law: its limitations / Major Ibrahim Hashim - Hashim, Ibrahim (Faculty of Law, 1989)
"The Provost must have a horse allowed him and some soldiers to attend him, and all the rest commanded to obey him, or else the service will suffer; for he is but one man and must correct many, and therefore he cannot be beloved. And he must be riding from one garrison to another to that the soldiers do not outrage nor scathe the country. "(1)Traditionally, the Military Police or commonly referred to as the Provost, originated in the Armies of early European Kingdoms in the days of the Norman conquest of England. The Provost were personnel specially selected . to arrest and keep in custody' military personnel found to be breaking the law. In order to execute their tasks, they had special powers conferred on them by the King in order to enforce and maintain discipline in the ranks while the Army campaigned actively in the field.